2014
DOI: 10.1016/j.jvs.2014.08.094
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after false lumen embolization with covered stent devices in chronic dissection

Abstract: Adjunctive false lumen embolization with a covered stent device promotes thrombosis and remodeling after stent grafting the true lumen for chronic dissection. Further study of this strategy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…At our institution, TEVAR has become a standard treatment for complicated CDIIIb aneurysms with suitable anatomy, and our previous study demonstrated acceptable short-term outcomes and relatively successful aortic remodeling (65% complete thrombosis rate) with aggressive TEVAR strategies [1]. Nevertheless, more than 30% of patients with chronic dissection exhibit patent FL, which is known to be associated with increased mortality and poor prognosis [1,9,[12][13][14][15]. Intimal tears below the celiac trunk, visceral branches and intercostal arteries from the FL, endoleaks, and stent-induced new entry tears remain as obstacles for favorable aortic remodeling and are limitations of TEVAR for CDIIIb aneurysms.…”
Section: Commentmentioning
confidence: 95%
See 2 more Smart Citations
“…At our institution, TEVAR has become a standard treatment for complicated CDIIIb aneurysms with suitable anatomy, and our previous study demonstrated acceptable short-term outcomes and relatively successful aortic remodeling (65% complete thrombosis rate) with aggressive TEVAR strategies [1]. Nevertheless, more than 30% of patients with chronic dissection exhibit patent FL, which is known to be associated with increased mortality and poor prognosis [1,9,[12][13][14][15]. Intimal tears below the celiac trunk, visceral branches and intercostal arteries from the FL, endoleaks, and stent-induced new entry tears remain as obstacles for favorable aortic remodeling and are limitations of TEVAR for CDIIIb aneurysms.…”
Section: Commentmentioning
confidence: 95%
“…Hybrid techniques, such as debranching, fenestrated endovascular aortic repair, or branched endovascular aortic repair, are feasible for CDIIIb aneurysms by extending aortic coverage and promoting aortic remodeling [16,17]. However, visceral debranching with extended distal aorta coverage is associated with significant morbidity and mortality, and not all patients are amenable to branched and fenestrated endografting [9,15,17,18]. Fenestration techniques, such as open fenestration or the knickerbocker technique, create a single lumen surgically or percutaneously to allow the stent graft to seal the FL aneurysm distally [16,19,20].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some techniques have been shown to occlude the false lumen and promote thrombosis and false-lumen remodeling. 4,5 The technique described here has some merit. The stent graft implanted into the false lumen completely blocked blood flow to the aneurysm and preserved blood flow to the celiac and renal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…4 This subset of patients may be treated with less invasiveness and a lower risk for spinal cord ischemia using standard endovascular repair to cover the proximal entry combined with techniques of direct false lumen occlusion, leaving the abdominal aorta and the iliac arteries untreated. [5][6][7][8] In this issue of the JEVT, Ogawa and colleagues 9 describe an alternative technique to create an extra-large occluding plug to achieve false lumen thrombosis in a patient with chronic type B aortic dissection and a 6-cm false lumen aneurysm in the proximal descending thoracic aorta. The authors used a 45-mm Excluder aortic extender (W.L.…”
mentioning
confidence: 99%